Pengaruh Rekrutmen, Seleksi, Dan Penempatan Karyawan Terhadap Kinerja Karyawan Pada PT Pos Indonesia Cabang Utama Semarang - Guruh Mulia Widayat; Wahyu Rizqy Amalinda; Teguh Ariefiantoro (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
This study aims to examine and analyze the effect of recruitment, selection, and placement of employees on the performance of employees of PT Pos Indonesia Main BranchSemarang. The research method used in this study uses quantitative methods. Thisresearch was conducted on 114 employees from various levels and departments at PTPos Indonesia Main Branch Semarang. The data collection technique uses thequestionnaire method which is then processed using the SPSS program. While the datatesting techniques used in this study include validity test, reliability test with AlphaCronhbach, normality test, multicollinearity test, heteroscedasticity test, multiple linearregression analysis, t test, and the coefficient of determination. The results of the analysis show that recruitment has no significant and negative effect on employee performance, selection has a positive and significant effect on employee performance, placement has no significant and negative effect on employee performance.